The effect offish density during transportation on hematological parameters, blood pH value and survival rate of juvenile snakeheads Channa striata (Bloch, 1793) - Wahyu Wahyu; Eddy Supriyono; Kukuh Nirmala; Enang Harris (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2015)
This research aimed to determine the density of juvenile snakeheads Channa striata during 24 hours transportation, which results in the highest survival rate, the lowest water quality changes, and the best physiological responses. Physiological responses are used as indicators of fish stress, consist of changes in blood pH value and changes in hematological profile. Research conducted at the laboratory scale with a completely randomized design, with the treatments in the form the density of fish during transport. The test fish used was juvenile of snakehead with an average weight of 2.5 g fish-1. The transport density that used was 30, 45, 60, and 75 fish bags-1. Every treatment has three replicates in the form of transportation bags. The result showed that treatment of a 30 fish bags-1 gave the best results with a survival rate of 98 % after transportation and this value was significantly different compared with other treatments (p<0,05). The changes in water quality also showed the lowest changes with ammonia level 0,031 mgNH3 L-1 and CO2 level 24 mgCO2 L-1 at the end of transportation. Physiological response at 0 hour after transportation also showed that treatment of a 30 fish bags-1 suffered lowest stress with blood pH value 7,59, total red blood cell 2,94 x 106 cel mm-3, total white blood cell 1,95 x 105 sel mm-3, hemoglobin 10,3 gr%, and hematocrit 25,8 %. These values considered as closest normal fish than other treatments. Abstrak Penelitian ini bertujuan untuk menentukan kepadatan benih ikan gabus selama pengangkutan 24 jam yang menghasil-kan tingkat kelangsungan hidup tertinggi, perubahan kualitas air terendah, dan respons fisiologis terbaik. Respons fisio-logis digunakan sebagai indikator stres yang dialami ikan, terdiri atas perubahan nilai pH darah dan perubahan gambar-an darah. Penelitian dilakukan pada skala laboratorium dengan Rancangan Acak Lengkap (RAL), dengan perlakuan be-rupa kepadatan ikan selama pengangkutan. Ikan uji yang digunakan adalah ikan gabus dengan bobot rata-rata 2,5 g per ekor. Kepadatan ikan selama pengangkutan yang digunakan yaitu 30, 45, 60, dan 75 ekor per kantong. Setiap perlakuan dilakukan tiga kali ulangan berupa kantong pengangkutan.Hasil penelitian menunjukkan bahwa perlakuan 30 ekor per kantong memberikan hasil terbaik. Nilai tingkat kelangsungan hidup yang dapat dicapai pada akhir pengangkutan sebe-sar 98% dan berbeda nyata dengan perlakuan lainnya (p<0,05). Perubahan kualitas air selama pengangkutan juga menunjukkan perubahan terendah, dengan konsentrasi amoniak sebesar 0,031 mgNH3 L